Dispersion method of carbon nanotube reinforced aluminum-based composite material
By preparing sheet aluminum powder, activated aluminum powder surface, dispersed carbon nanotube solution and vibration mixing methods, the problems of carbon nanotube structure damage and low production efficiency caused by high-energy ball milling are solved, and carbon nanotubes in aluminum are realized The uniform dispersion in matrix composite materials and the preparation of high-strength materials are suitable for industrial production.
Patent Information
- Application Number
- CN202411349887.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-26
- Publication Date
- 2024-12-17
- Estimated Expiration
- 2044-09-26
AI Technical Summary
When the existing high-energy ball milling method prepares carbon nanotube reinforced aluminum-based composite materials, it causes damage to the carbon nanotube structure, high cost and low production efficiency, and it is difficult to achieve uniform dispersion, which limits the mechanical and electrical properties of the materials and industrial production.
Low-cost and high-efficiency dispersion methods are adopted, including preparing sheet aluminum powder, activated aluminum powder surface, preparing dispersed carbon nanotube solution, vibrating powder mixing and vacuum drying, and protecting carbon nanotubes through alcohol dispersion media and vibrating powder mixing technology. The structure realizes its uniform dispersion in the aluminum-based composite material.
On the premise of ensuring the structural integrity of carbon nanotubes, it improves its dispersion in aluminum-based composite powder, reduces production costs, improves production efficiency, is suitable for large-scale industrial production, and realizes high-strength aluminum-based composite materials Preparation.
Smart Images

Figure CN119140827A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of preparing reinforced aluminum-based composite materials, and in particular relates to a dispersion method of carbon nanotube-reinforced aluminum-based composite materials. Background Art
[0002] With the development of materials science, carbon nanotubes are regarded as an ideal reinforcement material due to their unique mechanical and electrical properties, and are widely used in the preparation of high-performance metal-based composites. In particular, aluminum-based composites, which have the characteristics of light weight and high specific strength, have shown great application potential in the fields of aerospace, automobile manufacturing, electronic equipment, etc. However, achieving uniform dispersion of carbon nanotubes in aluminum-based composites is a technical challenge.
[0003] At present, high-energy ball milling is a commonly used dispersion method for preparing carbon nanotube-reinforced aluminum-based composites. This method uses mechanical force to smash carbon nanotubes into the aluminum matrix to achieve their dispersion in the aluminum matrix. Although this method can improve the dispersibility of carbon nanotubes to a certain extent, it has some significant limitations. First, the violent mechanical action during high-energy ball milling will cause serious structural damage to the carbon nanotubes, which will reduce their original mechanical and electrical properties, and increase their reactivity in the subsequent preparation process. In addition, the high-energy ball milling method has a high cost and low production efficiency, which is not conducive to large-scale industrial production.
[0004] Therefore, the present invention proposes a low-cost and high-efficiency dispersion method for carbon nanotube-reinforced metal-based composite materials, which improves the dispersibility of carbon nanotubes in aluminum-based composite material powder while ensuring the structural integrity of carbon nanotubes, and has great engineering significance for the preparation of high-strength aluminum-based composite materials. Summary of the invention
[0005] The present invention provides a method for dispersing a carbon nanotube-reinforced aluminum-based composite material, which specifically comprises the following steps: Step 1: preparing flaky aluminum powder; mixing aluminum powder, process control agent and grinding balls by high-energy ball milling to obtain flaky aluminum powder; Step 2: Activating the surface of the aluminum powder; heat treating the flaky aluminum powder obtained in step 1; Step 3: preparing a dispersed carbon nanotube solution; firstly, mixing the surfactant and the dispersion medium and subjecting them to electromagnetic stirring and heating treatment, then adding the carbon nanotubes and the electromagnetically stirred solution and subjecting them to ultrasonic dispersion treatment to obtain a uniformly dispersed carbon nanotube solution; Step 4: preparing carbon nanotube / aluminum slurry; firstly adding the dispersion medium to the carbon nanotube solution prepared in step 3, then adding the flaky aluminum powder prepared in step 2 and mixing, filling the flaked aluminum powder into a can and vibrating the flaked aluminum powder to obtain carbon nanotube / aluminum slurry; Step 5: preparing uniformly dispersed carbon nanotube / aluminum powder; vacuum drying the carbon nanotube / aluminum slurry obtained in step 4 to obtain uniformly dispersed carbon nanotube / aluminum powder.
[0006] Specifically, the aluminum powder in step 1 is spherical aluminum powder with a particle size of 15-53 μm, and the process control agent is stearic acid.
[0007] Specifically, the high-energy ball milling in step 1 adopts a planetary ball mill, the ball milling device adopts a 500ml zirconia jar and a 10mm zirconia grinding ball, the parameters of the high-energy ball milling are: the rotation speed is 200rpm, the high-energy ball milling mode is forward rotation for 10min, standing for 10min, reverse rotation for 10min, standing for 10min, and the cycle is carried out in sequence, and the high-energy ball milling time is 12h; after the high-energy ball milling is completed, it is cooled at room temperature for 8h, and the flaky aluminum powder is taken out using gloves filled with argon.
[0008] Specifically, the heat treatment temperature in step 2 is 400° C. and the insulation time is 2 h.
[0009] Specifically, the surfactant in step three is one of sodium dodecyl sulfate and sodium dodecylbenzene sulfonate, the dispersion medium is one of ethanol and isopropanol, and the carbon nanotubes have a diameter of 10-50 nm and a length of 0.5-30 μm.
[0010] Specifically, the rotation speed of the electromagnetic stirring process in step 3 is 200-500 rpm, the temperature is 40-50° C., and the time of the electromagnetic stirring is 30-50 min.
[0011] Specifically, during the ultrasonic dispersion treatment in step 3, the mass of the surfactant in the solution is 20% to 30% of the mass of the carbon nanotubes, the total mass of the prepared carbon nanotube solution is less than the mass of the flaky aluminum powder obtained in step 2, and the parameters of the ultrasonic dispersion are: power of 300 to 400 W, ultrasonic time of 0.5 to 2 h, and ultrasonic mode of ultrasonicating for 3 min, stopping for 1 min, and repeating the cycle in sequence.
[0012] Specifically, in step 4, the mass ratio of the total mass of the solution after adding the dispersion medium to the mass ratio of the flaky aluminum powder is 0.8:1 to 1.2:1.
[0013] Specifically, the parameters of the vibration powder mixing in step 4 are a frequency of 50-60 Hz and a time of 1-2 h; during the vibration powder mixing process, 10 mm large zirconia grinding balls and 5 mm small zirconia grinding balls are added to the powder mixing bottle, and their mass ratio is 5:1, and the total mass ratio of the large zirconia grinding balls and the small zirconia grinding balls to the mass ratio of the flaky aluminum powder is 1:1.
[0014] Specifically, during the vacuum drying process in step five, the carbon nanotube / aluminum slurry is located in a graphite mold, and the parameters of the vacuum drying are: vacuum degree <5 Pa, temperature 80-120° C., insulation time 6 h, and cooling time 6 h.
[0015] Compared with the prior art, the present invention has the following beneficial technical effects: (1) The present invention first grinds aluminum powder from spherical shape into flake shape by high-energy ball milling, thereby increasing the surface area of aluminum powder that can carry carbon nanotubes, which can be used as an effective method for preparing high-content carbon nanotubes; the dispersibility of carbon nanotubes in the ultrasonic process is improved by using alcohol dispersion medium, and the influence on the structure of carbon nanotubes is small.
[0016] (2) The present invention adopts a low-energy mixing method of vibration powder mixing to protect the integrity of the carbon nanotube structure. The vibration powder mixing process improves the dispersion uniformity of the carbon nanotubes and maintains the adsorption of the carbon nanotubes on the surface of the aluminum sheet.
[0017] (3) The solid-liquid ratio and ball-to-material ratio of the vibration powder mixing proposed in the present invention are key parameters for achieving uniform coating of carbon nanotubes on the surface of aluminum powder. The process is simple, the cost is low, and mass production can be achieved. BRIEF DESCRIPTION OF THE DRAWINGS
[0018] Figure 1 A schematic flow chart of a dispersion method of a carbon nanotube-reinforced aluminum-based composite material provided by the present invention; Figure 2 This is a SEM image of the powder morphology of the carbon nanotube / aluminum composite material prepared in Example 1 of the present invention; Figure 3 This is a SEM image of the powder morphology of the carbon nanotube / aluminum composite material prepared in Comparative Example 1 of the present invention; Figure 4 This is a SEM image of the powder morphology of the carbon nanotube / aluminum composite material prepared in Comparative Example 2 of the present invention; Figure 5 The Raman spectrum data comparison diagram of Example 1 of the present invention and Comparative Example 3 is shown. DETAILED DESCRIPTION
[0019] In order to make the purpose, technical solution and advantages of the embodiments of the present disclosure clearer, the technical solution of the embodiments of the present disclosure will be clearly and completely described below in conjunction with the accompanying drawings. Obviously, the described embodiments are part of the embodiments of the present disclosure, rather than all of the embodiments. Based on the described embodiments of the present disclosure, all other embodiments obtained by those skilled in the art without creative work also fall within the scope of protection of the present disclosure.
[0020] Unless otherwise defined, all terms (including technical and scientific terms) used herein have the same meaning as commonly understood by those skilled in the art to which the subject matter of the present disclosure belongs. It will be further understood that terms such as those defined in commonly used dictionaries should be interpreted as having a meaning consistent with their meaning in the context of the specification and the relevant art, and will not be interpreted in an idealized or overly formal form unless otherwise explicitly defined herein.
[0021] Reference to "embodiments" herein means that a particular feature, structure, or characteristic described in conjunction with the embodiments may be included in at least one embodiment of the present application. The appearance of the phrase "embodiments" in various locations in the specification does not necessarily refer to the same embodiment, nor is it an independent or alternative embodiment that is mutually exclusive with other embodiments. It is explicitly and implicitly understood by those skilled in the art that the embodiments described herein may be combined with other embodiments.
[0022] The present invention provides a dispersion method for carbon nanotube reinforced aluminum-based composite materials, which specifically comprises: Step 1: preparing flaky aluminum powder; mixing aluminum powder, process control agent and grinding balls by high-energy ball milling to obtain flaky aluminum powder; Step 2: Activating the surface of the aluminum powder; heat treating the flaky aluminum powder obtained in step 1; Step 3: preparing a dispersed carbon nanotube solution; firstly, mixing the surfactant and the dispersion medium and subjecting them to electromagnetic stirring and heating treatment, then adding the carbon nanotubes and the electromagnetically stirred solution and subjecting them to ultrasonic dispersion treatment to obtain a uniformly dispersed carbon nanotube solution; Step 4: preparing carbon nanotube / aluminum slurry; firstly adding the dispersion medium to the carbon nanotube solution prepared in step 3, then adding the flaky aluminum powder prepared in step 2 and mixing, filling the flaked aluminum powder into a can and vibrating and mixing the powder to obtain carbon nanotube / aluminum slurry; Step 5: preparing uniformly dispersed carbon nanotube / aluminum powder; vacuum drying the carbon nanotube / aluminum slurry obtained in step 4 to obtain uniformly dispersed carbon nanotube / aluminum powder.
[0023] In the present invention, the particle size of the aluminum powder in step one is spherical 15~53μm, the process control agent is stearic acid, and the specific process parameters of high-energy ball milling are: planetary ball milling, argon atmosphere protection, 500ml zirconia jar, 10mm zirconia grinding balls, ball-to-material ratio 5:1, rotation speed 200rpm, forward rotation 10min, standing 10min, reverse rotation 10min, standing 10min, and the cycle is carried out in sequence, and the cumulative ball milling time is 12h; after the high-energy ball milling is completed, the ball mill jar is cooled at room temperature for 8h and then the powder is taken out in a glove box filled with argon.
[0024] The heat treatment process in step 2 is to perform heat treatment under vacuum or hydrogen / argon atmosphere conditions, preferably hydrogen atmosphere conditions, at a temperature of 400° C. for 2 hours. After cooling to room temperature, the powder is taken out in a glove box filled with argon.
[0025] In step 3, the surfactant is an anionic surfactant such as sodium dodecyl sulfate (SDS) and sodium dodecylbenzene sulfonate (SDBS), the dispersion medium is an alcohol medium such as ethanol and isopropanol, the carbon nanotube has a diameter of 10-50 nm and a length of 0.5-30 μm, and is a multi-walled carbon nanotube. In the process of proportioning the carbon nanotube and the solution after electromagnetic stirring, the mass of the surfactant is 20%-30% of the mass of the carbon nanotube, for example, it can be 20%, 23%, 25%, 28%, 30%, and the total mass of the prepared carbon nanotube solution is less than the mass of the flaky aluminum powder prepared in step 2; the electromagnetic stirring speed is 200-500 rpm, the temperature is 40-50°C, and the time is 30-50 min; the ultrasonic dispersion process is 300-400 W, ultrasonic for 3 min, stop for 1 min, and repeat in sequence, and the total ultrasonic time is 0.5-2 h.
[0026] The mass ratio of the total mass of the solution after adding the dispersion medium in step 4 to the mass ratio of the flaky aluminum powder is preferably 0.8:1~1.2:1, for example, it can be 0.8:1, 1.0:1, 1.2:1, the volume of the carbon nanotube / aluminum slurry in the powder mixing bottle is preferably 1 / 3~1 / 2, and the specific process parameters of the vibration powder mixing are: frequency 50~60Hz, time 1~2h; the mass ratio of 10mm zirconia large grinding balls and 5mm zirconia small grinding balls is 5:1, and the ratio of the grinding ball mass to the flaky aluminum powder mass is 1:1.
[0027] Step 5: During the preparation of evenly dispersed carbon nanotube / aluminum powder, the carbon nanotube / aluminum slurry obtained in step 4 is directly poured into a graphite mold and vacuum dried. The specific process parameters are: temperature 80-120°C, insulation time 6h, and cooling time 6h.
[0028] The present invention will be further described below in conjunction with the embodiments. Example 1
[0029] A uniform dispersion method for preparing a carbon nanotube-reinforced aluminum-based composite material comprises the following steps: Step 1: Add 120g of 30μm spherical aluminum powder and 1% stearic acid to a zirconia ball mill, add 10mm zirconia grinding balls at a ball-to-material ratio of 5:1, and pass argon gas through the jar for 2-3 times - vacuum process. Place the jar in a planetary ball mill, speed 200rpm, forward 10min - stand 10min - reverse 10min - stand 10min, repeat until the total ball milling time reaches 12h. After standing at room temperature for 8h, take out the powder in a glove box filled with argon.
[0030] Step 2: The flaky aluminum powder obtained in step 1 is subjected to vacuum heat treatment at a temperature of 400° C. for 2 hours. After cooling to room temperature, the powder is taken out in a glove box filled with argon.
[0031] Step 3: Add 0.25g sodium dodecyl sulfate to 50g isopropanol, place the beaker in an electromagnetic stirrer for heating and stirring, with a speed of 300rpm, a temperature of 50°C, and a time of 30min. Immediately thereafter, add 0.75g carbon nanotubes to the solution for ultrasonic dispersion, and pour the solution into a jacketed beaker for a cold cycle during the ultrasonic process. The ultrasonic process is 300W, with 3min of ultrasonic on and 1min of off, and the cycle is repeated in sequence, with a total ultrasonic duration of 1h.
[0032] Step 4: Add isopropanol to the carbon nanotube dispersion containing 0.75g of carbon nanotubes to make the solution mass 75g, mix it with 75g of pure aluminum powder after ball milling, and pour it into a vibrating powder mixing bottle. Add 5:1 large and small zirconium oxide grinding balls into the bottle, and the mass ratio of grinding balls to aluminum powder is 1:2. Two vibrating powder mixing bottles of the same weight are symmetrically placed on the vibrating powder mixing machine. The vibrating powder mixing process is 60Hz frequency and 1h.
[0033] Step 5: Pour the mixed slurry obtained in step 4 directly into a graphite mold, put it into a vacuum drying oven, heat it to 80°C, keep it warm for 6 hours, and cool it for 6 hours.
[0034] The final carbon nanotube / aluminum composite powder morphology is as follows Figure 2 As shown, the carbon nanotubes are evenly dispersed on the surface of the aluminum powder, and there is no large-area exposure of the aluminum powder or agglomeration of the carbon nanotubes.
[0035] Comparative Example 1 This comparative example uses ultrasonic dispersion of aluminum powder and carbon nanotubes, which is a traditional ultrasonic dispersion process, to compare the beneficial effect of the present invention in achieving uniform dispersion of carbon nanotubes on aluminum powder. It includes the following steps: Step 1: Add 120g of 30μm spherical aluminum powder and 1% stearic acid to a zirconia ball mill, add 10mm zirconia grinding balls at a ball-to-material ratio of 5:1, and pass argon gas through the jar for 2-3 times to evacuate. Place the jar in a planetary ball mill at a speed of 200rpm, rotate forward for 10min-stand for 10min-reverse for 10min-stand for 10min, repeat until the total ball milling time reaches 12h, stop, stand at room temperature for 8h, and then take out the powder in a glove box filled with argon.
[0036] Step 2: The flaky aluminum powder obtained in step 1 is subjected to vacuum heat treatment at a temperature of 400° C. for 2 hours. After cooling to room temperature, the powder is taken out in a glove box filled with argon.
[0037] Step 3: Add 0.25g sodium dodecyl sulfate to 50g isopropanol, place the beaker in an electromagnetic stirrer for heating and stirring, with a speed of 300rpm, a temperature of 50°C, and a time of 30min. Immediately thereafter, add 0.75g carbon nanotubes to the solution for ultrasonic dispersion, and pour the solution into a jacketed beaker for a cold cycle during the ultrasonic process. The ultrasonic process is 300W, with 3min of ultrasonic on and 1min of off, and the cycle is repeated in sequence, with a total ultrasonic duration of 1h.
[0038] Step 4: Add 50g of isopropanol to the obtained carbon nanotube dispersion, mix it with 75g of aluminum powder in step 2, and continue to ultrasonicate the mixed solution. The ultrasonic process is 400W, ultrasonicate for 3min and stop for 1min, and repeat the process in sequence. The total ultrasonic time is 2h.
[0039] Step 5: Filter the mixed solution obtained in step 4, put it into a vacuum drying oven, heat it to 80°C, keep it warm for 6 hours, and cool it for 6 hours.
[0040] The final carbon nanotube / aluminum composite powder morphology is as follows Figure 3 As shown in the figure, the carbon nanotubes are not evenly dispersed, with large agglomerates appearing, and there are large areas of exposed aluminum powder surface and many scratches caused by ultrasonic impact, so the carbon nanotubes cannot be effectively coated on the aluminum powder surface.
[0041] Comparative Example 2 This comparative example provides an example in which the solid-liquid ratio in the vibration powder mixing process is greater than the maximum parameter designed by the technical solution, including the following steps: Step 1: Add 120g of 30μm spherical aluminum powder and 1% stearic acid to a zirconia ball mill, add 10mm zirconia grinding balls at a ball-to-material ratio of 5:1, and pass argon gas through the jar for 2-3 times - vacuum process. Place the jar in a planetary ball mill, speed 200rpm, forward 10min - stand 10min - reverse 10min - stand 10min, repeat until the total ball milling time reaches 12h. After standing at room temperature for 8h, take out the powder in a glove box filled with argon.
[0042] Step 2: The flaky aluminum powder obtained in step 1 is subjected to vacuum heat treatment at a temperature of 400° C. for 2 hours. After cooling to room temperature, the powder is taken out in a glove box filled with argon.
[0043] Step 3: Add 0.25g sodium dodecyl sulfate to 50g isopropanol, place the beaker in an electromagnetic stirrer for heating and stirring, with a speed of 300rpm, a temperature of 50°C, and a time of 30min. Immediately thereafter, add 0.75g carbon nanotubes to the solution for ultrasonic dispersion, and pour the solution into a jacketed beaker for a cold cycle during the ultrasonic process. The ultrasonic process is 300W, with 3min of ultrasonic on and 1min of off, and the cycle is repeated in sequence, with a total ultrasonic duration of 1h.
[0044] Step 4: Add isopropanol to the carbon nanotube dispersion containing 0.75g of carbon nanotubes to make the solution mass reach 150g, and mix it with 75g of pure aluminum powder after ball milling. At this time, the mass ratio of solution to powder is 2:1, which is greater than the 1.2:1 designed in the technical solution, and pour it into a vibrating powder mixing bottle. Add large and small zirconium oxide grinding balls in a ratio of 5:1 to the bottle, and the mass ratio of grinding balls to aluminum powder is 1:2. Two vibrating powder mixing bottles of the same weight are symmetrically placed on the vibrating powder mixing machine. The vibrating powder mixing process is a frequency of 60Hz and a time of 1h.
[0045] Step 5: Pour the mixed slurry obtained in step 3 directly into a graphite mold, put it into a vacuum drying oven, heat it to 80°C, keep it warm for 6 hours, and cool it for 6 hours.
[0046] The final carbon nanotube / aluminum composite powder morphology is as follows Figure 4 As shown, compared with the carbon nanotube / aluminum composite powder morphology of Example 1, it can be clearly seen that there is a large exposed area on the surface of the aluminum powder, the carbon nanotubes are severely agglomerated, and the dispersion is uneven, and the carbon nanotubes cannot be evenly and effectively coated on the aluminum powder surface. Therefore, the solid-liquid ratio designed by the technical solution is a decisive parameter in achieving the process of uniform dispersion of carbon nanotubes.
[0047] Comparative Example 3 This comparative example uses high-energy ball milling to disperse carbon nanotube / aluminum composite powder, which is the most commonly used dispersion method at present, but this method seriously damages the structure of carbon nanotubes, and is used to compare the beneficial effect of the present invention in protecting the structure of carbon nanotubes. It includes the following steps: Add 120g of 30μm spherical aluminum powder, 1% carbon nanotubes and 1% stearic acid to a zirconia ball mill, add 10mm zirconia grinding balls at a ball-to-material ratio of 5:1, and pass argon gas through the jar for 2-3 times - vacuum process. Place the jar in a planetary ball mill, rotate at 200rpm, rotate forward for 10min - stand for 10min - reverse for 10min - stand for 10min, repeat until the total ball milling time reaches 12h. After standing for 8h at room temperature, take out the powder in a glove box filled with argon.
[0048] Comparison of Raman spectra of the final carbon nanotube / aluminum composite powder and the composite powder obtained in the example Figure 5 As shown. In the Raman spectrum of carbon nanotubes, I D / I G Refers to the intensity ratio of the D band and the G band. The D band is located at about 1350cm -1 , which is related to the carbon atom lattice defects, while the G band is located at about 1580 cm -1 Nearby, it is related to the in-plane vibration of the SP2 hybridized carbon atoms. D / I G It is usually used to characterize the degree of disorder in the carbon nanotube structure. The higher the ratio, the greater the defects and disorder in the material. Figure 5 I D / I G It is calculated by calculating the D band (1000-1470cm -1 ) and near the G band (1470-1700cm -1 ) peak area ratio. D / I G is 1.32, the composite powder I obtained in the embodiment of the present invention D / I G is 1.35, while the composite powder I obtained in Comparative Example 3 D / I G It is 1.55. It can be concluded that the technical invention has a beneficial effect on the structural protection of carbon nanotubes compared with the high-energy ball milling process.
[0049] Finally, it should be noted that the above embodiments are only used to illustrate the technical solution of the present invention rather than to limit it. Although the present invention has been described in detail with reference to the preferred embodiments, those skilled in the art should understand that the technical solution of the present invention can be modified or replaced by equivalents without departing from the spirit and scope of the technical solution of the present invention.
Claims
1. A dispersion method for carbon nanotube-reinforced aluminum-based composite materials, It is characterized in that The method comprises the following steps: Step 1: preparing flaky aluminum powder; mixing aluminum powder, a process control agent and a grinding ball by high-energy ball milling to obtain flaky aluminum powder; Step 2: Activating the surface of the aluminum powder; heat treating the flaky aluminum powder obtained in step 1; Step 3: preparing a dispersed carbon nanotube solution; firstly, mixing the surfactant and the dispersion medium and subjecting them to electromagnetic stirring and heating treatment, then adding the carbon nanotubes and the electromagnetically stirred solution and subjecting them to ultrasonic dispersion treatment to obtain a uniformly dispersed carbon nanotube solution; Step 4: preparing carbon nanotube / aluminum slurry; firstly adding the dispersion medium to the carbon nanotube solution prepared in step 3, then adding the flaky aluminum powder prepared in step 2 and mixing, filling the flaked aluminum powder into a can and vibrating the flaked aluminum powder to obtain carbon nanotube / aluminum slurry; Step 5: preparing uniformly dispersed carbon nanotube / aluminum powder; vacuum drying the carbon nanotube / aluminum slurry obtained in step 4 to obtain uniformly dispersed carbon nanotube / aluminum powder.
2. The method for dispersing a carbon nanotube-reinforced aluminum-based composite material according to claim 1, It is characterized in that The aluminum powder in step 1 is spherical aluminum powder with a particle size of 15-53 μm, and the process control agent is stearic acid.
3. The method for dispersing a carbon nanotube-reinforced aluminum-based composite material according to claim 1, It is characterized in that The high-energy ball milling in step 1 adopts a planetary ball mill, and the ball milling device adopts a 500ml zirconia jar and a 10mm zirconia grinding ball. The parameters of the high-energy ball milling are: the rotation speed is 200rpm, the high-energy ball milling mode is forward rotation for 10min, standing for 10min, reverse rotation for 10min, standing for 10min, and the cycle is carried out in sequence. The high-energy ball milling time is 12h; after the high-energy ball milling is completed, it is cooled at room temperature for 8h, and the flaky aluminum powder is taken out using gloves filled with argon.
4. The method for dispersing a carbon nanotube-reinforced aluminum-based composite material according to claim 1, It is characterized in that The heat treatment temperature in step 2 is 400° C. and the holding time is 2 h.
5. The method for dispersing a carbon nanotube-reinforced aluminum-based composite material according to claim 1, It is characterized in that In step 3, the surfactant is one of sodium dodecyl sulfate and sodium dodecylbenzene sulfonate, the dispersion medium is one of ethanol and isopropanol, and the carbon nanotubes have a diameter of 10-50 nm and a length of 0.5-30 μm.
6. The method for dispersing a carbon nanotube-reinforced aluminum-based composite material according to claim 1, It is characterized in that The rotation speed of the electromagnetic stirring process in step 3 is 200-500 rpm, the temperature is 40-50° C., and the time of the electromagnetic stirring is 30-50 min.
7. The method for dispersing a carbon nanotube-reinforced aluminum-based composite material according to claim 1, It is characterized in that During the ultrasonic dispersion treatment in step 3, the mass of the surfactant in the solution is 20% to 30% of the mass of the carbon nanotubes, the total mass of the prepared carbon nanotube solution is less than the mass of the flaky aluminum powder obtained in step 2, and the ultrasonic dispersion parameters are: power of 300 to 400 W, ultrasonic time of 0.5 to 2 h, ultrasonic mode of ultrasonic 3 min, stop 1 min, and repeat in sequence.
8. The method for dispersing a carbon nanotube-reinforced aluminum-based composite material according to claim 1, It is characterized in that In step 4, the total mass ratio of the solution after adding the dispersion medium to the flaky aluminum powder is 0.8:1 to 1.2:
1.
9. The method for dispersing a carbon nanotube-reinforced aluminum-based composite material according to claim 1, It is characterized in that The parameters of the vibration powder mixing in step 4 are a frequency of 50-60 Hz and a time of 1-2 h. During the vibration powder mixing process, 10 mm large zirconia grinding balls and 5 mm small zirconia grinding balls are added to the powder mixing bottle in a mass ratio of 5:1, and the total mass ratio of the large zirconia grinding balls and the small zirconia grinding balls to the mass ratio of the flaky aluminum powder is 1:
1.
10. The method for dispersing a carbon nanotube-reinforced aluminum-based composite material according to claim 1, It is characterized in that During the vacuum drying process in step five, the carbon nanotube / aluminum slurry is located in a graphite mold, and the parameters of the vacuum drying are: vacuum degree <5 Pa, temperature 80-120° C., insulation time 6 h, and cooling time 6 h.
Citation Information
Patent Citations
Preparation method of graphene reinforced metal-matrix composite
CN102329976A
Graphene nanosheet / aluminum composite and preparation method thereof
CN110578076A
Preparation method of uniform carbon nanotube solution
CN113600074A
Method for preparing carbon nanotube reinforced aluminum-based composite material through solid-liquid method
CN113789457A
Method for uniformly dispersing discontinuous reinforcements in high-strength aluminum alloy
CN115229197A
